IMPLEMENTATION OF THE CONTEXT INPUT PROCESS AND PRODUCT (CIPP) MODEL IN THE TEACHER PROFESSIONAL DEVELOPMENT PROGRAM STATE ALIYAH MADRASAH BY THE MINISTRY OF RELIGION IN RIAU PROVINCE - Fahrurazi; Martinis Yamin; Kasful Anwar Us (European Journal of Humanities and Educational Advancements, 2023)
This study aims to examine the application of the context input process and product (CIPP) model to the professional development program for Madrasah Aliyah Negeri teachers by the Ministry of Religion in Riau Province. This study uses a qualitative method with an evaluative approach. Intensive data mining was then analyzed carefully at each stage. The research phase for the evaluation of teacher professionalism development programs in MAN throughout Riau Province refers to the CIPP design model. This model consists of four components, namely context, input, process, and product. The data used in this research comes from primary data and secondary data. Primary data, namely data that comes directly from the leaders and staff of the Ministry of Religion throughout Riau, the madrasa development department and teachers, supervisors, and heads of State Islamic Senior High Schools throughout Riau, while the data collection techniques in this study were observation, interviews, and documentation. The data analysis technique used in this evaluative research consists of three streams of activities or processes that occur simultaneously, namely: data reduction, data presentation, and conclusion/verification. The analysis shows that the MAN teacher development program in Riau has succeeded in increasing the number of MAN teachers who obtain educator certificates, and teachers are very enthusiastic when shown to attend training or workshops. However, there is still a need for increased guidance for improving teacher competence, as well as guidance for guidance for promotion and functional positions of teachers who have been certified. Another thing that needs to be considered is the absence of clear standard operating procedures for program support staff, so that the ability of implementing staff to carry out their functions is still not optimal.